Effectiveness of Dialogical Patrol of Samapta Uniti in Pressing Number Action Criminal Motorcycle Theft Use Guard Public Order and Maintenance in Region Law of Kediri City Police Office - Nathaniel, john nanda; Iswanto, Ganang; Gibran Gani Mandica, Andi (Akademi Kepolisian Republik Indonesia, 2025)
The crime of motorcycle theft is one of the criminal cases that is in the public spotlight. City Kediri Because between Action Criminal 3C, motorcycle theft, which owns several reports in 2021, there were 17 cases; in 2022, there were 21 cases; and in 2023, there were 30 cases of motorcycle theft. If there is no effective active patrol, especially dialogic patrols, the security and comfort of the people of Kediri City will be disrupted. This study aims to determine the implementation and inhibiting factors and support active patrol dialogic units in press number criminal act motorcycle theft use, guard public order, and security in regional law police station Kediri City. This study uses SWOT theory and POAC management theory and uses the concepts of effectiveness, patrol concept, and criminal crime. The author also applies a descriptive qualitative method in this study by collecting data through observation, interviews, and document studies. The data was then tested using various sources, techniques, time, and theories of triangulation. The results and conclusions of the study indicate that the implementation of patrols, especially dialogical patrols of the Satsamapta Polres Kediri City, cannot be said to be effective because several things have not been appropriately implemented. Good guidelines for operational police, among them, quality And the number of human resources owned, the implementation of dialogic patrol activities, and direct supervision from leaders to reduce the number of motorcycle theft crimes to maintain public order and security in the jurisdiction of the Kediri City Police.